“La vaporización como alternativa al uso del bromuro de metilo en la desinfección de camas almacigueras en la producción de plántulas de tabaco” - Pizango Piña, Jorge Enrique (2003)
The vaporization is a method of control of plagues and illnesses that are mainly in the soil that you to initiate at the beginning of last century, had controlled overgrowths, worms, nematodes, until bacteria's amonificadoras. The T3 (90 'x 30 cm}, the T6 (substratum with BM} and the T1 (60'x 30 cm} they were the treatments that threw the biggest averages in height and diameter of the shaft, growth root, air biomass, biomass root respectively. The T3(90 ' x 30cm}, T1 (60 ' x 30cm}, T6(8.M}, the treatments that threw the smallest averages of nodules in the roots were. The treatments T1 (60'x 30 cm), T2 (60'x 40 cm}, T3 (90 'x 30 cm), T4 (90'x 40 cm} and T6 (BM} with averages of statistically you equal to each other, they overcame statistically to the treatment witness in the control of nematodes as: Meloidoigyne sp., Pratylenchus sp., Helicotylenchus sp., Aphelenchus sp., and Tylenchus sp., mushrooms like Phytophthora sp., and Fusarium sp., overgrowths of wide and narrow leaf as Portulaca sp., Amaranthus sp., Euphorbia sp., of wide leaf and Rottboellia sp., Cyperus sp., of narrow leaf respectively, present in the substratum, demonstrating the high efficiency of the vaporization in the control of nematode and comparatively similar to the use of the Methyl bromide.